ANALISIS INSTAGRAM ADS DALAM AKUISISI PELANGGAN PADA DIBANTUIN.ID - Annisa Nadaa Shabrina; Dyana Rachmawati; Nadia Nurfadilla; Windy Amelia Putri; Siti Monalisa (Jurnal Ilmiah Rekayasa dan Manajemen Sistem Informasi, 2022)
Dibantuin.id is a creative design agency which is a service that is engaged in making creative strategies that can help businesses to achieve these business goals. In carrying out promotional activities, dibantuin.id has usedInstagram social media. However, it is not yet known which media is more effective for carrying out such advertising, whether video media or image media. By utilizing CRM in the field of operations (campaign management), paid advertising is one solution to the promotion field of dibantuin.id. However, in the use of paid advertising on social media, of course there is a difference in the number of audience engagement revenue on advertising. Therefore, the purpose of this study is how to determine the audience's characteristics in advertisements carried out through video and image media. The T-test model was used in this study to see a comparison of the two media within a period of 12 days in advertising aided dibantuin.id on Instagram social media. After doing research, it was found that dibantuin.id was more effective in using video media in promoting on Instagram ads.